Pengaruh Kepemimpinan Transformasional Terhadap Motivasi Kerja dalam Pandangan New Public Management - Detson Ray Halomoan Sitorus; Dimas Agustian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of transformational leadership on work motivation in the view of the new public management. This study uses a quantitative paradigm and uses a saturated sample technique, with a total sample of fourteen employees. The data collection method used in this study was a questionnaire which was then analyzed using frequency analysis and simple linear regression analysis. The study results show that transformational leadership positively and significantly affects employee motivation. Work motivation possessed by employees can fulfill what is expected in the view of the new public management, including fast and adaptive service to change. In conclusion, there is a significant influence between transformational leadership and work motivation in the view of the new public management. Keywords: New Public Management; Transformational Leadership; Work Motivation